Comparative techno-economic assessment of sugarcane biorefineries producing glutamic acid, succinic acid, levulinic acid and xylitol from A-molasses and lignocellulosic biomass - Morakile, Tumelo (Stellenbosch : Stellenbosch University, 2021)
Thesis (MEng)--Stellenbosch University, 2021.